Mitochondria-related parameters of lymphocyte subsets can distinguish different disease stages in patients with HBV infection - Zhiqi Liu; Bin Yin; Liang Xu; Yan Yu; Yongfeng Yang; Xuping Wu (Scientific Reports)
Abstract To explore the difference of peripheral immune indexes especially T subsets cell mitochondrial indexes in patients with chronic HBV infection (CHB), liver cirrhosis (LC), hepatocellular carcinoma (HCC) and healthy controls (HCs). From May 2023 to December 2023, HBV infected patients aged 40–59 years (HBV infection group, 236 cases) and healthy people of the same age group (control group, 112 cases) were selected as the study objects. More than 80 parameters related to lymphocyte including cell percentage, absolute count, mitochondrial mass and mitochondrial low membrane potential were obtained by flow cytometry. The mitochondrial mass of memory T cells was found to be sequentially raised in the disease progression of hepatitis B patients from CHB to LC and eventually to HCC, and mitochondrial low membrane potential ratio was sequentially decreased. Then we screened out 4 main indicators related to the stage of disease progression in HBV-infected patients and distinguished the differences among the control group, CHB, LC, and HCC groups through the calculation of MPOLS (mitochondrial parameters of lymphocyte subsets) value, which can be used as a novel biomarker for hepatitis B disease progression. Mitochondrial parameters of peripheral lymphocytes in HBV-infected patients are significant indicators of different stages of disease progression. The MPOLS provides rich clinical data support for clinical early warning of high-risk hepatitis B patients, and we believe that the MPOLS can be combined with a variety of clinical characteristics to achieve more accurate diagnosis and treatment.